Additional Sex Combs-Like 2 Is Required for Polycomb Repressive Complex 2 Binding at Select Targets - Lai, Hsiao-Lei (Public Library of Science, 2013)
Polycomb Group (PcG) proteins are epigenetic repressors of gene expression. The Drosophila Additional sex combs (Asx) gene and its mammalian homologs exhibit PcG function in genetic assays; however, the mechanism by which Asx family proteins mediate gene repression is not well understood. ASXL2, one of three mammalian homologs for Asx, is highly expressed in the mammalian heart and is required for the maintenance of cardiac function. We have previously shown that Asxl2 deficiency results in a reduction in the bulk level of histone H3 lysine 27 trimethylation (H3K27me3), a repressive mark generated by the Polycomb Repressive Complex 2 (PRC2). Here we identify several ASXL2 target genes in the heart and investigate the mechanism by which ASXL2 facilitates their repression. We show that the Asxl2-deficient heart is defective in converting H3K27me2 to H3K27me3 and in removing ubiquitin from mono-ubiquitinated histone H2A. ASXL2 and PRC2 interact in the adult heart and co-localize to target promoters. ASXL2 is required for the binding of PRC2 and for the enrichment of H3K27me3 at target promoters. These results add a new perspective to our understanding of the mechanisms that regulate PcG activity and gene repression.